Case report: A case of unilateral combined central retinal vein occlusion, incomplete central retinal artery occlusion, and papillitis following a third dose of COVID-19 vaccination - Furukawa, Ami; Suzuki, Yukihiko; Nozuki, Narumi; Kurosaka, Naruki; Kogawa, Satomi; Hara, Shinya; Ueno, Shinji (Frontiers in Ophthalmology, 2024)
Purpose The aim of this study was to present a case of severe visual loss due to retinal arteriovenous occlusion and papillitis in one eye following vaccination against coronavirus disease (COVID-19). Methods A 45-year-old man undergoing treatment for hypertension had severely reduced visual acuity in the right eye 1 day after receiving a third dose of a COVID-19 vaccine manufactured by Moderna. Clinical examination showed that the best-corrected visual acuity in the right eye was counting fingers. Other findings included circumferential retinal hemorrhage, perimacular ischemic color, severe macular edema, and severe optic disc swelling, indicating the presence of central retinal vein occlusion, incomplete central retinal artery occlusion, and papillitis. Based on the possibility of post-vaccination inflammation and/or abnormal immune response, three courses of steroid pulse therapy were administered, and the visual acuity slightly improved to 20/1,000. Results Three months after the onset of symptoms, macular edema disappeared; conversely, retinal thinning of the macula and extensive non-perfusion areas mainly on the nasal side were noted. Conclusion The findings in this case suggest that inflammation and abnormal immune response after receiving a COVID-19 vaccination may lead to combined retinal arteriovenous occlusion and papillitis.